2007
DOI: 10.1016/j.wocn.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic strengthening of German fricatives in duration and assimilatory devoicing

Abstract: This study addressed prosodic effects on the duration of and amount of glottal vibration in German word-initial fricatives /f, v, z/ in assimilatory and non-assimilatory devoicing contexts. Fricatives following /a/ (non-assimilation context) were longer and were produced with less glottal vibration after higher prosodic boundaries, reflecting domain initial prosodic strengthening. After /t/ (assimilation context), lenis fricatives (/v, z/) were produced with less glottal vibration than after /a/, due to assimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 43 publications
2
24
1
1
Order By: Relevance
“…For example, Kohler and Künzel [1979] report with regard to voice assimilation in French that the assimilation towards voicing or voicelessness need not affect the duration and formant patterns that are related to the voicevoiceless distinction in the adjacent vowel. Similar observations were made for English by Smith [1997] and Myers [2010] as well as for German by Kuzla et al [2007].…”
Section: Discussionsupporting
confidence: 85%
“…For example, Kohler and Künzel [1979] report with regard to voice assimilation in French that the assimilation towards voicing or voicelessness need not affect the duration and formant patterns that are related to the voicevoiceless distinction in the adjacent vowel. Similar observations were made for English by Smith [1997] and Myers [2010] as well as for German by Kuzla et al [2007].…”
Section: Discussionsupporting
confidence: 85%
“…In these sentences, we can expect prosodic boundaries larger than a word boundary before the target word, but smaller than, for instance, an Intonation Phrase boundary. We chose two different sentence types to elicit these types of boundaries (Types B and C), because it is unclear from the literature (e.g., Fé ry, 1993;Fox, 1993;Grabe, 1998) whether they indeed elicit intermediate prosodic boundaries (but see Kuzla, Cho, & Ernestus, 2007). Finally, a large prosodic boundary can be expected between the syntactically complete sentences in Type D, where orthography requires a period.…”
Section: Speech Materialsmentioning
confidence: 99%
“…The Minor category was characterized by a boundary tone, but no pause, and the Word category by the absence of both a pause and a boundary tone. These criteria have been applied in other studies before (Bombien et al, 2010;Cho & McQueen, 2005;Kuzla et al, 2007;Kuzla, Ernestus, & Mitterer, 2010). The two trained native listeners then coded the boundary tones separately, by listening to the utterances and considering the f0 plots in PRAAT.…”
Section: Prosodic Categorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed, among other things, that voiceless stops such as /p/ in the word support /s=pLrt/ maintain their characteristic aspiration when following [s] in cases of schwa elision, in contrast with underlying /sp/ clusters, which notably lack aspiration after the [p] release. Other connected speech phenomena now claimed to be gradient rather than categorical include nasal place assimilation in English (Byrd, 1996;Nolan, 1992, but see Ellis & Hardcastle, 2002 for evidence of categorical assimilation in some speakers), palatalization of /s/ before /j/ in English (Zsiga, 1995), and progressive voice assimilation in German (Kuzla, Cho, & Ernestus, 2007).…”
Section: Introductionmentioning
confidence: 99%